The theory of the numerical-analytic method: Achievements and new trends of development. VI - Ronto, M. I.; Samoilenko, A. M.; Trofimchuk, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We analyze the application of the numerical-analytic method proposed by A.M. Samoilenko in 1965 to multipoint boundary-value problems.